The The Role of Government Internal Supervisory Apparatus and Corruption Control on Regional Independence - Deswita Martinez; Rudy Usman; Latifah Sukmawati Yuniar (STIE Malangkucecwara, 2026)
This study aims to examine the role of the government internal supervisory apparatus (APIP) and corruption control in enhancing regional fiscal independence. Regional fiscal independence refers to the condition where local governments can manage their finances autonomously without relying on central government funds. The study uses data from 1,018 observations consisting of provincial/regency/city governments in Indonesia during 2021-2022, with a final sample of 509 after excluding 33 regions lacking corruption control data. The main findings show that APIP’s capacity for effective supervision positively contributes to corruption control and ultimately increases regional fiscal independence. Regions with strong internal supervision tend to have more transparent and accountable budget management, reducing dependence on central funds. Furthermore, the study reveals that the age of the regional government, government status, and geographic location also significantly affect the level of fiscal independence. Therefore, strengthening APIP capacity and improving the effectiveness of corruption control should be prioritized to achieve sustainable regional fiscal independence.